Processes and design for manufacturing - El Wakil, Sherif D., 1944- (CRC Press, 2025)
"Processes and Design for Manufacturing, 4th edition, offers a comprehensive and detailed examination of modern manufacturing processes, while also delving into the concept of Design for Manufacturing (DFM) and its application across diverse manufacturing techniques. This book examines manufacturing processes from the viewpoint of the product designer, investigating the selection of manufacturing methods in the early phases of design and how this affects the constructional features of a product. The stages from design process to product development are examined, integrating an evaluation of cost factors. The text emphasizes both a general design orientation and a systems approach and covers topics such as additive manufacturing, concurrent engineering, polymeric and composite materials, cost estimation, design for assembly, and environmental factors. This edition has new and updated chapters, including a detailed chapter focusing on the prominent topic of microchip manufacturing. This book is essential reading for senior undergraduate students studying manufacturing processes, product design, design for manufacture and computer-aided manufacturing"-- Provided by publisher.
Keywords: Manufacturing processes.; Metal-work.; Computer integrated manufacturing systems.; elektronické knihy; electronic books